Myocardial Viability: What We Knew and What Is New - Adel Shabana; Ayman El-Menyar (Cardiology Research and Practice)
Some patients with chronic ischemic left ventricular dysfunction have shown significant improvements of contractility with favorable long-term prognosis after revascularization. Several imaging techniques are available for the assessment of viable myocardium, based on the detection of preserved perfusion, preserved glucose metabolism, intact cell membrane and mitochondria, and presence of contractile reserve. Nuclear cardiology techniques, dobutamine echocardiography and positron emission tomography are used to assess myocardial viability. In recent years, new advances have improved methods of detecting myocardial viability. This paper summarizes the pathophysiology, methods, and impact of detection of myocardial viability, concentrating on recent advances in such methods. We reviewed the literature using search engines MIDLINE, SCOUPS, and EMBASE from 1988 to February 2012. We used key words: myocardial viability, hibernation, stunning, and ischemic cardiomyopathy. Recent studies showed that the presence of viable myocardium was associated with a greater likelihood of survival in patients with coronary artery disease and LV dysfunction, but the assessment of myocardial viability did not identify patients with survival benefit from revascularization, as compared with medical therapy alone. This topic is still debatable and needs more evidence.